Different hydrodynamic model for gas-phase propylene polymemation in a catalytic fluidized bed reactor - Shamiri, A.; Hussain, Mohd Azlan; Mjalli, F.S.; Mostoufi, N. (2010)
A comparative simulation study was carried out using the improved well-mixed, constant bubble size and well mixed models. These fluidized bed reactor models, combined with comprehensive kinetics for propylene homo-polymerization in the presence of a multiple active site Ziegler-Natta catalyst. In the improved model, the effect of the presence of particles in the bubbles and the excess gas in the emulsion phase was taken into account to improve the quantitative understanding of the actual fluidized bed process. The superficial gas velocity and catalyst feed rate have a strong effect on the hydrodynamics and reaction rate, which results in a greater variation in the polymer production rate and reactor temperature. At typical operating conditions the improved well mixed and well mixed models were in good agreement. While the COO!ICU bubble size model was found to over-predict the emulsion phase temperature and underpredict propylene concentration.